BEHAVIOUR ANALYSIS OF SHEARWALL-FRAME INTERACTION ON BUILDING STRUCTURE USING KIYOSHI MUTO METHOD AND SOFTWARE ANALYSIS ETABS - SINAGA, NOVALIN
Nowadays, the use of shear walls in high-rise buildings is commonly used. The higher the building, will be more affected to earthquake. Shear walls are one that has an important role in resisting lateral loads or earthquake loads. The use of shear walls in the structure can increase the lateral stiffness of the structure and reduce the lateral displacement of the structure. In addition to increasing stiffness and reducing displacement, shear walls are also used to make interstory drift each floors more uniform. The proportion of lateral loads received by shear walls is large enough so that the calculation of the forces on the shear walls needs to be done properly and accurately because it greatly affects the percent error in the overall structure. In the building planning process, the use of structural analysis software ETABS has become a very common thing to use. However, the results from structural analysis software ETABS cannot absolutely be used because there is no detailed explanation of the analysis and assumptions of calculations made by the software. One of the manual calculation methods used to determine the deformation of shear wall is the Kiyoshi Muto method. The analysis using a research model of 10 and 30 story frame-shear wall structure. The analysis will be to determine shear deformation coefficient of free-standing shearwall for rectangular cross section and be obtained the value is 1. The number of meshing 4x4 is effective and efficient enough to be used for 2D and 3D models to obtain an analysis of deformation and internal forces with shear walls.